Towards improvement of the electrochemical properties of ionic liquid-containing polyethylene oxide-based electrolytes. (1st May 2017) - Simonetti, E.; Carewska, M.; Di Carli, M.; Moreno, M.; De Francesco, M.; Appetecchi, G.B.
Graphical abstract: Abstract: We report an investigation on quaternary, polyethylene oxide (PEO)-based electrolytes as separators for lithium polymer batteries. The target is the development of Li + conducting membranes, containing large fraction of the N -methyl- N -propylpyrrolidinium bis(fluorosulfonyl)imide ionic liquid, able to combine fast ion transport properties with improved electrochemical stability. The PEO electrolytes, prepared through a fully-dry solvent-free procedure, exhibited good aging resistance and conductivity values equal to 3.46×10 −4 and 2.43×10 −3 S cm −1 at −20 and 20 °C, respectively, combined with an anodic stability up to 4.5 V ( vs . Li°/Li + ). These results represent the best performance, in terms of ion transport properties and electrochemical stability, reported till now for PEO electrolytes.